Penerapan Media Pembelajaran Interaktif Lumi Education untuk Meningkatkan Hasil Belajar Siswa pada Pelajaran Pendidikan Pancasila - Santika, Indah; Mushlihuddin, Rahmat; Harahap, Anita Santi (ALSYS, 2025)
This study is motivated by the limited research on the application of interactive technology-based learning media in the subject of Pancasila Education at the elementary school level, despite the fact that this phenomenon significantly impacts students' interest and learning outcomes. The purpose of this study is to analyze the effectiveness of using Lumi Education games to improve students' learning outcomes on the material of religious diversity symbols in Indonesia. The method used is Classroom Action Research (CAR) with a descriptive quantitative design through a two-cycle approach. The subjects of the study consisted of 19 students from Class IIC at SD Negeri 060913 Medan, selected purposively. Data were collected through observation and learning outcome tests, and then analyzed using descriptive percentage statistics. The results indicate a significant increase in student and teacher activity as well as student learning outcomes from Cycle I to Cycle II, with the average score rising from 70.71 to 83.57 and the completeness of learning reaching 85.71%. These findings align with the objectives of the study and reinforce constructivist learning theory and technology-based learning theory, which emphasize the importance of active student engagement. The main conclusion of this study is that Lumi Education media is effective in improving learning outcomes and student engagement in Pancasila Education. The implications of this research include theoretical aspects in the form of literature enrichment on interactive media in character education, as well as practical aspects in the form of recommendations for teachers and elementary schools to integrate engaging and interactive digital media to create more meaningful learning experiences. This research also opens opportunities for further studies on the optimization of the Lumi Education platform in different educational materials and levels.